Composite particles and method for producing the same
Patent Information
- Application Number
- JP2023129002
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-06-15
- Filing Date
- 2023-08-08
- Publication Date
- 2025-04-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing cellulose derivative particles used in cosmetics lack sufficient dispersibility in hydrophobic solvents and formulations, relying heavily on particle shape for tactile sensation and light scattering effects.
Composite particles are formed by coating cellulose derivative particles with a surface treatment compound that is soluble in water and/or organic solvents, such as cationic surfactants or fatty acid soaps, to enhance dispersibility and texture.
The composite particles achieve high dispersibility and improved tactile sensation in various cosmetic compositions, providing a uniform film that enhances texture and light scattering effects.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] The present disclosure relates to composite particles and a method for producing the same. More particularly, the present disclosure relates to composite particles containing cellulose derivative particles and a method for producing the same. [Background technology]
[0002] Conventionally, various polymer microparticles have been blended into cosmetics for the purposes of improving the spreadability of cosmetics, changing the texture, imparting a wrinkle-blurring effect, and improving the slipperiness of foundations and other products. Microparticles made of synthetic polymers such as polyamide, polymethyl methacrylate (PMMA), polystyrene, polypropylene, and polyethylene have been used as the microparticles blended into such cosmetics. However, in recent years, due to the problem of marine pollution caused by microplastics, there has been a demand for microparticles made of environmentally friendly non-synthetic polymer materials as an alternative to these synthetic polymers, which have the necessary properties.
[0003] As a non-synthetic polymer, the application of fine particles made of cellulose derivatives derived from the natural product cellulose has been investigated. For example, Patent Document 1 discloses cellulose acetate particles having an average particle size of 80 nm to 100 μm, a sphericity of 0.7 to 1.0, a surface smoothness of 80% to 100%, and a total degree of acetyl substitution of 0.7 to 2.9.
[0004] Patent Document 2 discloses cellulose derivative particles having an alkoxy group having two or more carbon atoms or an acyl group having three or more carbon atoms, the cellulose derivative particles having an average particle size of 80 nm to 100 μm, a sphericity of 70% to 100%, a surface smoothness of 80% to 100%, and a total degree of substitution of 0.7 to 3.
[0005] Patent Document 3 discloses particles containing cellulose acetate having an average particle size of 80 nm to 100 μm, a sphericity of 0.7 to 1.0, a surface smoothness of 80% to 100%, a surface contact angle with water of 100° or more, and a total degree of acetyl substitution of 0.7 to 2.9. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent No. 6609726 [Patent Document 2] Japanese Patent Publication No. 2020-152851 [Patent Document 3] Patent No. 6694559 Summary of the Invention [Problem to be solved by the invention]
[0007] The microparticles disclosed in Patent Documents 1-3 are said to provide a good texture and a light scattering (soft focus) effect suitable for cosmetic compositions. However, these effects depend largely on the particle shape, such as sphericity and surface smoothness. Furthermore, various solvents are used in cosmetic compositions depending on the application, and the formulation of the formulation may be changed. High dispersibility in hydrophobic solvents and formulations is required for polymer microparticles incorporated into cosmetic compositions. The particle dispersibility of previously proposed microparticles still leaves room for improvement.
[0008] An object of the present disclosure is to provide composite particles that have a good feel and excellent particle dispersibility regardless of particle shape, and a method for producing the same. [Means for solving the problem]
[0009] The composite particles according to the present disclosure comprise cellulose derivative particles and a coating covering the surface of the particles. The coating is formed from a surface treatment compound that is soluble in water and / or an organic solvent.
[0010] The organic solvent may be an alcohol.
[0011] The surface treatment compound is one or more selected from the group consisting of cationic surfactants, fatty acid soaps, and cationic polymers. The surface treatment compound may be one or more selected from the group consisting of distearyldimethylammonium chloride, behenyltrimethylammonium chloride, stearyltrimethylammonium chloride, potassium stearate, sodium stearate, polyoctanium-61, and polyoctanium-67.
[0012] Preferably, the content of the surface treatment compound is 0.1% by weight or more and 20% by weight or less.
[0013] Preferably, the cellulose derivative has an alkoxy group having 2 to 20 carbon atoms or an acyl group having 2 to 40 carbon atoms. The cellulose derivative may be cellulose acylate. The cellulose derivative may be cellulose acetate.
[0014] Preferably, the total degree of substitution of the cellulose derivative is 0.7 or more and 3.2 or less.
[0015] The cellulose derivative particles may have an average particle size of 0.08 μm or more and 10 μm or less, a sphericity of 0.7 or more and 1.0 or less, and a surface smoothness of 80% or more and 100% or less.
[0016] The cosmetic composition of the present disclosure contains any of the composite particles described above.
[0017] The method for producing composite particles of the present disclosure includes: (1) A mixing step of stirring and mixing cellulose derivative particles and a surface treatment compound in a solvent that dissolves the surface treatment compound. and (2) After the mixing step, a drying step is performed in which the solid content including the cellulose derivative particles is washed and dried. The solvent may be water or an alcohol. Preferably, the amount of the surface treatment compound added is 0.1% by weight or more and 20% by weight or less relative to the cellulose derivative particles. [Effects of the Invention]
[0018] According to the composite particles according to the present disclosure, a coating formed from the surface treatment compound provides a good feel to the touch, and high particle dispersibility is achieved in various solvents and formulations used in cosmetic compositions. [Brief explanation of the drawings]
[0019] [Figure 1] FIG. 1 is an SEM image of a composite particle according to one embodiment of the present disclosure. [Figure 2] 1 is a diagram illustrating a method for evaluating surface smoothness (%). [Figure 3] 1 is a diagram illustrating a method for evaluating surface smoothness (%). DETAILED DESCRIPTION OF THE INVENTION
[0020] An example of a preferred embodiment will be described in detail below. Each configuration and combination thereof in each embodiment is merely an example, and addition, omission, substitution, and other modifications of configurations are possible as appropriate within the scope of the present disclosure. The present disclosure is not limited by the embodiments, but only by the scope of the claims. Furthermore, each aspect disclosed in this specification can be combined with any other feature disclosed in this specification.
[0021] In the present specification, the range "X to Y" means "X or more and Y or less." Unless otherwise noted, all tests were carried out at room temperature (20°C ± 5°C).
[0022] [Composite particles] The composite particles of the present disclosure comprise cellulose derivative particles and a coating covering the particle surface. The coating is formed from a surface treatment compound that dissolves in water and / or alcohols. Cellulose derivative particles having a coating made of a surface treatment compound on their surface have an excellent feel to the touch. The coating provides the composite particles with surface properties that are suitable for solvents and formulations used in cosmetic compositions. The composite particles achieve high particle dispersibility in various solvents and formulations.
[0023] Here, "composite particles" are defined as particles consisting of a core and a coating covering the core, with the core and coating being formed from different materials. That is, in the present disclosure, the core is a cellulose derivative particle, and the coating is formed from a surface treatment compound. The shape of the cellulose derivative particle as the core is not particularly limited as long as the effects of the present disclosure can be obtained.
[0024] FIG. 1 shows a scanning electron microscope photograph (3000x magnification) of a composite particle according to one embodiment of the present disclosure. As shown in FIG. 1, the surface of the composite particle is uniform. It can be seen that in this composite particle, a coating made of a surface treatment compound is formed almost uniformly on the surface of the cellulose derivative particles. As long as the effects of the present disclosure are obtained, the coating may be physically attached to the surface of the cellulose derivative particles, or the surface treatment compound forming the coating may be chemically bonded to the cellulose derivative.
[0025] [Surface treatment compounds] In the composite particles of the present disclosure, the surface treatment compound forming the coating is soluble in water and / or an organic solvent. Examples of organic solvents include alcohols and ketones. Examples of alcohols include monohydric alcohols such as methanol, ethanol, propanol, isopropanol, and butanol, polyhydric alcohols such as ethylene glycol, propylene glycol, 1,3-butylene glycol, and glycerin, and amino alcohols. Examples of ketones include acetone and ethyl acetate.
[0026] In the method for producing composite particles described below, water and / or an organic solvent is used as a solvent for forming a film by a wet processing method. From the viewpoints of easy mixing and stirring and easy removal after film formation, a surface treatment compound that is soluble in water and / or alcohols is preferred, and a surface treatment compound that is soluble in water or an alcohol having 1 to 8 carbon atoms is preferred.
[0027] Here, "dissolved" means that no cloudiness or precipitation is visually observed when at least 0.1 g of the surface treatment compound is added to and mixed with 100 ml of solvent at 25° C. In the composite particles of the present disclosure, the amount of the surface treatment compound dissolved in 100 ml of solvent at 25° C. is preferably 0.1 wt % or more, more preferably 0.5 wt % or more, and even more preferably 1.0 wt % or more.
[0028] In the present disclosure, the type of surface treatment compound that is soluble in water and / or an organic solvent is not particularly limited, but from the viewpoint of improving dispersibility in solvents and formulations used in cosmetic compositions, one or more types selected from the group consisting of cationic surfactants, fatty acid soaps, and cationic polymers are preferred.
[0029] Examples of cationic surfactants include quaternary ammonium salts and / or amine salts having a long-chain alkyl group. From the viewpoint of improving the feel and particle dispersibility, quaternary ammonium salts represented by the following general formula (1) are preferred. R 1 R 2 R 3 R 4 N + X - (1) (In the formula, X - is a halogen ion, and R 1 , R 2 , R 3 and R 4 are each independently an alkyl group having 1 to 25 carbon atoms which may have a substituent, and R 1 , R 2 , R 3 and R 4 At least one of the groups is an alkyl group having 12 or more carbon atoms. Specific examples of the cationic surfactant represented by formula (1) include distearyl dimethyl ammonium chloride, behenyl trimethyl ammonium chloride, stearyl trimethyl ammonium chloride, distearyl diethyl ammonium chloride, decyl triethyl ammonium chloride, decyl dimethyl hydroxyethyl ammonium chloride, coconut oil trimethyl ammonium chloride, coconut oil methyl dihydroxyethyl ammonium chloride, myristyl trimethyl ammonium chloride, lauryl trimethyl ammonium chloride, distearyl dimethyl ammonium bromide, and stearyl trimethyl ammonium bromide.
[0030] In the present disclosure, fatty acid soaps are defined as alkali metal salts of higher fatty acids. The higher fatty acids are preferably fatty acids having 12 to 25 carbon atoms, and may be saturated or unsaturated. Examples of such fatty acid soaps include sodium or potassium salts of lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, oleic acid, linoleic acid, α-linolenic acid, and erucic acid. Examples of cationic polymers include polyoctaniums such as polyoctanium-61 and polyoctanium-67.
[0031] From the viewpoint of easily obtaining a good feel and high particle dispersibility, preferred surface treatment compounds are one or more selected from the group consisting of distearyldimethylammonium chloride, alkyltrimethylammonium chloride, stearyltrimethylammonium chloride, potassium stearate, sodium stearate, polyoctanium-61, and polyoctanium-67.
[0032] From the viewpoint of obtaining surface properties suitable for incorporation into cosmetic compositions, the content of the surface-treated compound in the composite particles is preferably 0.1 wt% or more, more preferably 1.0 wt% or more. From the viewpoint of not impairing the physical properties of the cellulose derivative particles, the content of the surface-treated compound is preferably 20 wt% or less, more preferably 5.0 wt% or less, and particularly preferably 2.0 wt% or less. The content of the surface-treated compound in the composite particles may be 0.1 wt% to 20 wt%, 0.1 wt% to 5.0 wt%, 0.1 wt% to 2.0 wt%, 1.0 wt% to 20 wt%, 1.0 wt% to 5.0 wt%, or 1.0 wt% to 2.0 wt%. When two or more surface-treated compounds are used in combination, it is preferable that their total content falls within the above range. The content of the surface-treated compound can be adjusted by the amount added in the mixing step of the production method described below.
[0033] [Cellulose derivative particles] The average particle size of the cellulose derivative particles may be 0.08 μm or more and 100 μm or less, 0.1 μm or more, 1 μm or more, 2 μm or more, or 4 μm or more. It may also be 80 μm or less, 40 μm or less, 20 μm or less, or 14 μm or less. An average particle size of 100 μm or less further improves the tactile feel and light scattering (soft focus) effect. Cellulose derivative particles with an average particle size of 0.08 μm or more are easy to produce. The tactile feel includes the feel on the skin when the cellulose derivative particles are directly touched, as well as the feel on the skin when the cellulose derivative particles are incorporated into a cosmetic composition, for example.
[0034] The average particle size can be measured using dynamic light scattering. Specifically, the procedure is as follows: First, cellulose derivative particles are added to pure water to a concentration of 100 ppm, and a pure water suspension is prepared using an ultrasonic vibration device. Then, the volume frequency particle size distribution is measured using a laser diffraction method (HORIBA, Ltd., "Laser Diffraction / Scattering Particle Size Distribution Analyzer LA-960," 15 minutes of ultrasonic treatment, refractive index 1.500, medium (water; 1.333)). In this volume frequency particle size distribution, the particle size corresponding to 50% of the cumulative scattering intensity is determined as the average particle size. In other words, the average particle size (μm) in this specification is the volume-based median size.
[0035] The particle size variation coefficient of the cellulose derivative particles may be 0% or more and 60% or less, or 2% or more and 50% or less. The particle size variation coefficient (%) can be calculated by dividing the standard deviation of the particle sizes by the average particle size x 100.
[0036] The sphericity of the cellulose derivative particles is preferably 0.7 to 1.0, more preferably 0.8 to 1.0, and even more preferably 0.9 to 1.0. If the sphericity is 0.7 or more, a better feel to the touch can be obtained, and for example, when the particles are incorporated into a cosmetic composition, the feel on the skin and the soft focus effect can be further improved.
[0037] Sphericity can be measured by the following method. Using images of particles observed with a scanning electron microscope (SEM), the long and short diameters of 30 randomly selected particles are measured, the short diameter / long diameter ratio of each particle is calculated, and the average value of these short diameter / long diameter ratios is taken as the sphericity. The closer the sphericity is to 1, the more truly spherical the particle is considered to be.
[0038] The surface smoothness of the cellulose derivative particles is preferably 80% to 100%, more preferably 85% to 100%, and even more preferably 90% to 100%. A surface smoothness of 80% or more provides a better feel to the touch. The closer to 100%, the more preferable the feel to the touch.
[0039] A method for measuring surface smoothness will be described below, using examples of sample particles with low surface smoothness, with reference to FIGS. 2 and 3. Surface smoothness can be determined by taking a scanning electron micrograph of the particle, observing the irregularities on the particle surface, and then based on the area of the irregularities. Specifically, a scanning electron micrograph of the particle is taken at 2500 to 5000 times the magnification of the particle (see FIG. 2 for an example of a particle micrograph), and the image is binarized using an image processing device, Winroof (manufactured by Mitani Shoji Co., Ltd.) (see FIG. 3 for a binarized image of the micrograph of FIG. 2). The area ratio of the concave portions (shaded areas) of the irregularities in any region smaller than the particle, including the center and / or vicinity of the particle (e.g., the regions indicated by n1 and n2 in FIG. 3), is then calculated, and the surface smoothness (%) of the particle is calculated using the following formula: The size of the region may be 5 μm square when the particle diameter is 15 μm. Surface smoothness of one particle (%) = (1 - concave area ratio) x 100 Concave area ratio = concave area in the given area / given area In the present disclosure, the surface smoothness (%) is the average value of the surface smoothness of 10 randomly selected particle samples, that is, n1 to n10. The higher this value, the higher the surface smoothness.
[0040] The cellulose derivative constituting the cellulose derivative particles of the present disclosure preferably has an alkoxy group having 2 to 20 carbon atoms or an acyl group having 2 to 40 carbon atoms. The cellulose derivative may have both an alkoxy group having 2 to 20 carbon atoms and an acyl group having 2 to 40 carbon atoms.
[0041] The number of carbon atoms in the alkoxy group of the cellulose derivative may be 3 or more, or 5 or more. The number of carbon atoms in the alkoxy group may be 15 or less, and preferably 8 or less. The cellulose derivative may have two or more types of alkoxy groups with different numbers of carbon atoms. The cellulose derivative may also have both an alkoxy group with 2 to 20 carbon atoms and an alkoxy group with 1 carbon atom (methoxy group).
[0042] Examples of alkoxy groups having 2 to 20 carbon atoms include ethoxy, protoxy, butoxy, pentoxy, hexoxy, heptoxy, and octoxy groups. These alkoxy groups may have a substituent, as long as the effects of the present disclosure are obtained.
[0043] The number of carbon atoms in the acyl group of the cellulose derivative may be 3 or more, or 4 or more. The number of carbon atoms in the acyl group may be 30 or less, 18 or less, or 16 or less. The cellulose derivative may have two or more types of acyl groups with different numbers of carbon atoms.
[0044] Examples of the acyl group having 2 to 40 carbon atoms include an acetyl group, a propionyl group, a butyryl group, a pentanoyl (valeryl) group, a hexanoyl group, a heptanoyl group, an octanoyl group, a nonanoyl group, an undecanoyl group, a dodecanoyl group, a tridecanoyl group, a tetradecanoyl (myristoyl) group, a pentadecanoyl group, a hexadecanoyl group, a heptadecanoyl group, and an octadecanoyl (stearoyl) group. These acyl groups may have a substituent, as long as the effects of the present disclosure are obtained.
[0045] From the viewpoint of obtaining a good feel and particle dispersibility suitable for a cosmetic composition, a cellulose derivative having an acyl group having 2 to 40 carbon atoms (i.e., cellulose acylate) is preferred. Preferred acyl groups are one or more selected from an acetyl group, a propionyl group, and a butyryl group, and more preferably an acetyl group. The cellulose derivative of the present disclosure may be cellulose acetate.
[0046] The cellulose derivative constituting the cellulose derivative particles may have a total degree of substitution of 0.7 to 3.2, 1.0 to 3.2, 1.4 to 3.1, or 2.0 to 3.0, because this facilitates the production of particles with excellent moldability and a pleasant feel.
[0047] The total degree of substitution of a cellulose derivative can be measured by the following method. First, the total degree of substitution of a cellulose derivative is the sum of the degrees of substitution at the 2-, 3-, and 6-positions of the glucose ring of the cellulose derivative. The degrees of substitution at the 2-, 3-, and 6-positions of the glucose ring of the cellulose derivative can be measured by NMR according to the method of Tezuka (Tezuka, Carbonydr. Res. 273, 83 (1995)). Specifically, the free hydroxyl groups of the cellulose derivative are acylated with a carboxylic acid anhydride in pyridine. The type of carboxylic acid anhydride used here should be selected depending on the purpose of analysis. For example, acetic anhydride is suitable for analyzing the propionyl substitution degree of cellulose acetate propionate, and propionic anhydride is suitable for analyzing the acetyl substitution degree. The solvent and acid anhydride used in the acylation reaction can be selected appropriately depending on the cellulose derivative to be analyzed.
[0048] The acylated sample was dissolved in deuterated chloroform. 13 C-NMR spectrum is measured. For example, when the substituent is an acetyl group, a propionyl group, or a butyryl group, the carbon signal of the acetyl group appears in the region of 169 ppm to 171 ppm in the order of 2, 3, and 6 from the upfield, the carbonyl carbon signal of the propionyl group appears in the region of 172 ppm to 174 ppm in the same order, and the carbon signal of the butyryl group appears in the region of 171 ppm to 173 ppm in the order of 2, 3, and 6 from the upfield. For another example, when analyzing a cellulose derivative having a propionyl group, or when analyzing the degree of propionyl substitution after treating a cellulose derivative without a propionyl group with propionic anhydride, the carbonyl carbon signal of the propionyl group appears in the same order in the region of 172 ppm to 174 ppm.
[0049] The total degree of substitution of cellulose derivatives treated with carboxylic acid anhydride using Tezuka's method or methods based on it is 3.0. Therefore, the sum of the areas of the carbonyl carbon signals of the acyl groups originally present in the cellulose derivative and the carbonyl signals of the acyl groups introduced by carboxylic acid anhydride treatment can be normalized to 3.0, and the abundance ratio of acetyl groups to propionyl groups at the corresponding positions (area ratio of each signal) can be calculated to determine the degree of acyl substitution at the 2-, 3-, and 6-positions of the glucose ring in the original cellulose derivative. Needless to say, the only acyl-containing substituents that can be analyzed using this method are those that do not correspond to the carboxylic acid anhydride used for the analytical treatment.
[0050] However, if the total degree of substitution at the 2nd, 3rd, and 6th positions of the glucose ring of the sample cellulose derivative is 3.0 and it is known in advance that all of the substituents are limited, such as acetyl and propionyl groups, the acylation step can be omitted and the sample can be directly dissolved in deuterated chloroform and subjected to NMR spectroscopy. As with the case where the acylation step is included, if all of the substituents are acetyl and propionyl groups, the carbon signals of the acetyl groups appear in the 169 to 171 ppm region from the high magnetic field in the order of 2nd, 3rd, and 6th positions, and the carbon signals of the propionyl groups appear in the same order in the 172 to 174 ppm region. Therefore, the degree of substitution, such as the degree of acetyl and propionyl substitution at the 2nd, 3rd, and 6th positions of the glucose ring of the cellulose derivative, can be determined from the abundance ratio of the acetyl and propionyl groups at the corresponding positions (in other words, the area ratio of each signal).
[0051] The cellulose derivative particles may or may not contain a plasticizer. In the present disclosure, a plasticizer refers to a compound that can increase the plasticity of a cellulose derivative. The plasticizer is not particularly limited, and examples thereof include adipic acid-based plasticizers, citric acid-based plasticizers, glutaric acid-based plasticizers, succinic acid-based plasticizers, sebacic acid-based plasticizers, glycerin ester-based plasticizers, neopentyl glycol, and phosphoric acid-based plasticizers. The cellulose derivative particles may contain two or more plasticizers. One or more plasticizers selected from the group consisting of acetyltriethyl citrate, triacetin, and diacetin are preferred.
[0052] When the cellulose derivative particles contain a plasticizer, the content of the plasticizer in the cellulose derivative particles is not particularly limited, and may be, for example, more than 0% by weight and not more than 40% by weight, 2% by weight or more and not more than 40% by weight, 10% by weight or more and not more than 30% by weight, or 15% by weight or more and not more than 20% by weight, relative to the weight of the cellulose derivative particles.
[0053] The content of the plasticizer in the cellulose derivative particles is determined by dissolving the cellulose derivative particles in a solvent capable of dissolving the cellulose derivative particles, and then measuring the amount of the plasticizer in the solution. 1 It can be determined by measuring with H-NMR.
[0054] [Cosmetic composition] The composite particles of the present disclosure have an excellent texture and disperse well in various solvents or formulations, making them suitable for use in cosmetic compositions. A cosmetic composition containing these composite particles fills in and smooths unevenness in the skin, and by scattering light in various directions, it is possible to obtain a soft focus effect that makes wrinkles and other imperfections less noticeable.
[0055] Cosmetic compositions include foundations such as liquid foundations and powder foundations; concealers; sunscreens; makeup bases; lipsticks and lipstick bases; face powders such as body powders, pressed face powders, and pressed powder eye shadows; wrinkle-concealing creams; and topical skin and hair preparations primarily intended for cosmetic purposes, such as skin care lotions, and are not limited in their formulation. Formulations may include liquids such as aqueous solutions, emulsions, and suspensions; semisolids such as gels and creams; and solids such as powders, granules, and solids. They may also be emulsions such as creams and emulsions; oil gels such as lipsticks; powders such as foundations; and sol-gels such as hair styling products.
[0056] [Method of manufacturing composite particles] The method for producing composite particles according to the present disclosure includes a mixing step and a drying step. The mixing step involves stirring and mixing cellulose derivative particles and a surface-treated compound in a solvent capable of dissolving the surface-treated compound, thereby adhering the surface-treated compound to the surfaces of the cellulose derivative particles. The solvent used in this mixing step is water and / or an organic solvent. The drying step involves collecting the cellulose derivative particles with the surface-treated compound attached as a solid, washing them, and drying them.
[0057] According to this manufacturing method, cellulose derivative particles and a surface treatment compound are mixed in an appropriate solvent selected from water and / or an organic solvent, whereby the surface treatment compound can be adhered substantially uniformly to the particle surfaces. By drying the particles, a coating of the surface treatment compound is formed on the surfaces of the cellulose derivative particles.
[0058] The solvent selected from water and / or organic solvents is not particularly limited as long as it can dissolve the surface treatment compound. Examples of organic solvents include alcohols and ketones. Examples of alcohols include monohydric alcohols such as methanol, ethanol, propanol, isopropanol, and butanol, polyhydric alcohols such as ethylene glycol, propylene glycol, 1,3-butylene glycol, and glycerin, and amino alcohols. Examples of ketones include acetone and ethyl acetate. Two or more solvents may be used in combination.
[0059] From the viewpoints of safety and ease of removal in the drying step described below, water and / or alcohols are preferred, water and / or alcohols that are easily miscible with water are more preferred, and one or more selected from the group consisting of water, butanol, and octanol are even more preferred.
[0060] The surface treatment compound used in the manufacturing method of the present disclosure is preferably one or more selected from the group consisting of cationic surfactants, fatty acid soaps, and cationic polymers. Specific examples of cationic surfactants, fatty acid soaps, and cationic polymers are as described above. More preferably, the surface treatment compound is one or more selected from the group consisting of distearyldimethylammonium chloride, behenyltrimethylammonium chloride, stearyltrimethylammonium chloride, potassium stearate, sodium stearate, polyoctanium-61, and polyoctanium-67.
[0061] In the manufacturing method of the present disclosure, the amount of the surface treatment compound added is not particularly limited and is appropriately adjusted depending on the physical properties of the cellulose derivative particles, the type of surface treatment compound, etc. From the viewpoint of facilitating film formation, the amount of the surface treatment compound added is preferably 0.1 wt % or more, more preferably 1.0 wt % or more, relative to the cellulose derivative particles. From the viewpoint of reducing aggregation during drying, the amount of the surface treatment compound added is preferably 20 wt % or less, more preferably 5.0 wt % or less, and particularly preferably 2.0 wt % or less. The amount of the surface treatment compound added may be 0.1 wt % to 20 wt %, 0.1 wt % to 5.0 wt %, 0.1 wt % to 2.0 wt %, 1.0 wt % to 20 wt %, 1.0 wt % to 5.0 wt %, or 1.0 wt % to 2.0 wt %. When two or more surface treatment compounds are used in combination, the total amount added preferably satisfies the above range.
[0062] In the mixing step, the method for mixing the cellulose derivative particles and the surface treatment compound is not particularly limited. The cellulose derivative particles and the surface treatment compound weighed in a predetermined ratio may be simultaneously added to water and / or an organic solvent, or the cellulose derivative particles may be added to a solution in which a predetermined amount of the surface treatment compound is dissolved in water and / or an organic solvent, and then mixed.
[0063] The mixing temperature may be any temperature at which the surface treatment compound dissolves. For example, the mixing temperature may be 50°C or lower, 40°C or lower, or 30°C or lower. From the viewpoint of energy saving and cost reduction, mixing at room temperature is preferred. The mixing time may be appropriately adjusted depending on the production scale, mixing temperature, etc.
[0064] After the mixing step, the method for collecting the solid content containing the cellulose derivative particles is not particularly limited, and known methods such as filtration and centrifugation may be used. As described above, the collected cellulose derivative particles have a surface treatment compound attached thereto. The cellulose derivative particles are dried to remove the solvent and form a coating made of the surface treatment compound, thereby obtaining the composite particles of the present disclosure.
[0065] In the manufacturing method of the present disclosure, the drying method is not particularly limited, and known methods such as heat drying, reduced pressure drying, and vacuum drying can be used. From the viewpoint of high drying efficiency, the drying temperature is preferably room temperature or higher, and may be 50°C or higher, or may be 60°C or higher. From the viewpoint of suppressing thermal degradation of the surface treatment compound, the drying temperature is preferably 120°C or lower.
[0066] [Method of producing cellulose derivative particles] The method for producing cellulose derivative particles is not particularly limited, and known methods can be used. For example, cellulose derivative particles may be obtained by a production method including: a first step of mixing a desired cellulose derivative with a plasticizer to obtain a cellulose derivative impregnated with the plasticizer; a second step of kneading the cellulose derivative impregnated with the plasticizer with a water-soluble polymer to obtain a dispersion containing the cellulose derivative impregnated with the plasticizer as a dispersoid; and a third step of removing the water-soluble polymer from the dispersion to obtain cellulose derivative particles. This production method produces substantially spherical particles with high surface smoothness and sphericity, thereby further improving the tactile feel of the composite particles of the present disclosure.
[0067] The plasticizer used in the first step is not particularly limited as long as it has a plasticizing effect in the melt extrusion processing of the cellulose derivative. Specifically, the plasticizers described above can be used alone or in combination of two or more as the plasticizer contained in the cellulose derivative particles. One or more selected from the group consisting of acetyltriethyl citrate, triacetin, and diacetin are preferred.
[0068] The amount of plasticizer may be more than 0 part by weight and not more than 40 parts by weight, 2 parts by weight or more and not more than 40 parts by weight, 10 parts by weight or more and not more than 30 parts by weight, or 15 parts by weight or more and not more than 20 parts by weight, relative to 100 parts by weight of the total amount of cellulose derivative and plasticizer. By using the amount of plasticizer in this range, particles with higher sphericity can be obtained.
[0069] The cellulose derivative and the plasticizer can be mixed in a dry or wet manner using a mixer such as a Henschel mixer. When a mixer such as a Henschel mixer is used, the temperature inside the mixer may be set to a temperature at which the cellulose derivative does not melt, for example, in the range of 20°C or higher and lower than 200°C.
[0070] The cellulose derivative and the plasticizer may be mixed by melt kneading. The melt kneading can be performed by heating and mixing the cellulose derivative and the plasticizer in an extruder. The kneading temperature (cylinder temperature) of the extruder may be 200°C to 230°C. Even at a temperature in this range, plasticization can be performed to obtain a uniform kneaded product. The kneaded product may be extruded in the form of a strand and then formed into a pellet shape by hot cutting or the like. In this case, the die temperature may be about 220°C.
[0071] The water-soluble polymer used in the second step refers to a polymer that has an insoluble content of less than 50% by weight when 1 g of the polymer is dissolved in 100 g of water at 25°C. Preferred water-soluble polymers are polyvinyl alcohol, polyethylene glycol, and thermoplastic starch, with polyvinyl alcohol and thermoplastic starch being more preferred. Thermoplastic starch can be obtained by known methods. Specifically, tapioca starch can be mixed with approximately 20% glycerin as a plasticizer and kneaded in a twin-screw extruder.
[0072] The amount of the water-soluble polymer may be 55 to 99 parts by weight, preferably 60 to 90 parts by weight, and more preferably 65 to 85 parts by weight, per 100 parts by weight of the total amount of the cellulose derivative impregnated with the plasticizer and the water-soluble polymer.
[0073] In the second step, the cellulose derivative impregnated with the plasticizer and the water-soluble polymer can be kneaded in an extruder such as a twin-screw extruder. The preferred kneading temperature (cylinder temperature) is 200°C or higher and 280°C or lower. The dispersion may be extruded in the form of a string from a die attached to the tip of the extruder such as a twin-screw extruder, and then cut into pellets. In this case, the die temperature may be 220°C or higher and 300°C or lower.
[0074] The dispersion obtained in the second step is a dispersion containing a water-soluble polymer as a dispersion medium and a cellulose derivative impregnated with a plasticizer as a dispersoid. In other words, the dispersion is composed of a water-soluble polymer as a sea component and a cellulose derivative impregnated with a plasticizer as island components. In this dispersion, the kneaded material constituting the island components contains a cellulose derivative and a plasticizer and is mainly spherical.
[0075] In the third step, the water-soluble polymer is removed from the dispersion to obtain cellulose derivative particles. The method for removing the water-soluble polymer from the dispersion is not particularly limited, as long as it can dissolve the water-soluble polymer and remove it from the particles. For example, a method of dissolving and removing the water-soluble polymer in the dispersion using a solvent such as water; an alcohol such as methanol, ethanol, or isopropanol; or a mixture thereof can be used. Specifically, for example, a method of removing the water-soluble polymer from the dispersion by mixing the dispersion with a solvent and then separating the solvent containing the dissolved water-soluble polymer by solid-liquid separation such as filtration can be used. When removing the water-soluble polymer by stirring and mixing the dispersion with a solvent and then filtering, the stirring and filtering steps can be repeated multiple times to increase the removal efficiency.
[0076] In the third step, the plasticizer may or may not be removed from the dispersion together with the water-soluble polymer, and the resulting cellulose derivative particles may or may not contain a plasticizer.
[0077] The mixing ratio of the dispersion to the solvent may be 0.01% by weight or more and 20% by weight or less, 2% by weight or more and 15% by weight or less, or 4% by weight or more and 13% by weight or less, based on the total weight of the dispersion and the solvent. When the mixing ratio of the dispersion to the solvent is within this range, efficient washing becomes possible and solid-liquid separation after washing becomes easy.
[0078] The mixing temperature of the dispersion and the solvent is preferably 0°C or higher and 200°C or lower, more preferably 20°C or higher and 110°C or lower, and even more preferably 40°C or higher and 80°C or lower. By keeping the mixing temperature within this range, the water-soluble polymer is efficiently removed and deformation and aggregation of particles due to heating are suppressed. The mixing time of the dispersion and the solvent is appropriately adjusted depending on the mixing temperature, etc.
[0079] [Method of producing cellulose derivatives] The method for producing the cellulose derivative is not particularly limited, and the cellulose derivative can be produced by a known production method.
[0080] When the cellulose derivative is a cellulose ester, it can be produced, for example, by a process of activating raw pulp (cellulose), acylating the activated cellulose with an esterifying agent (acylating agent), deactivating the acylating agent after the acylation reaction, and aging (saponification, hydrolysis) the resulting cellulose acylate. Before the activation process, a pretreatment process may be included in which the raw pulp is disintegrated and crushed, and then sprayed with acetic acid. After the aging process (saponification, hydrolysis), a posttreatment process may be included in which the cellulose acylate is precipitated, purified, stabilized, and dried.
[0081] When the cellulose derivative is a cellulose ether, it can be produced by immersing raw pulp (cellulose) in a mixture of a lower aliphatic alcohol such as isopropyl alcohol (IPA) or tertiary butanol (TBA), water, and an alkali metal hydroxide such as sodium hydroxide to obtain alkali cellulose, which serves as a precursor to the cellulose ether, and then adding an etherifying agent to form a slurry (precipitation). Before the alkali cellulose-obtaining step, a pretreatment step may be included in which the raw pulp is disintegrated and crushed, and then acetic acid is sprayed and mixed. After the slurry (precipitation) step, a posttreatment step may be included in which the pulp is separated by precipitation, purified, stabilized, and dried. [Example]
[0082] The effects of the present disclosure will be clarified below by examples, but the present disclosure should not be interpreted as being limited based on the description of these examples.
[0083] [Example 1] Distearyldimethylammonium chloride (product name "Cation DSV" manufactured by Sanyo Chemical Industries, Ltd.) was added as a surface treatment compound to pure water and dissolved, and then cellulose acetate particles (manufactured by Daicel Corporation, total substitution degree = 2.4, average particle size 7.1 μm) as cellulose derivative particles were added to a concentration of 5 wt%, and the mixture was stirred for 1 hour at room temperature under an air atmosphere. The amount of distearyldimethylammonium chloride added was 1.5 wt% relative to the cellulose acetate particles.
[0084] After stirring, the mixture was filtered under pressure, and the solid matter obtained was poured into pure water and stirred for 30 minutes to wash the solid matter. In the same manner, the filtration-washing process was repeated three times, and the resulting solid matter was vacuum-dried at 80°C for 24 hours to obtain composite particles of Example 1. The content of the surface compound in the resulting composite particles was 1.3 wt%.
[0085] [Example 2-28] Composite particles of Examples 2-28 were obtained in the same manner as in Example 1, except that the types and amounts of cellulose derivative particles and surface treatment compounds were as shown in Tables 1-4 below. However, in Examples 7, 14, and 21, the surface treatment compound, Polyoctanium-61, was dissolved in 1-butanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) instead of pure water. A scanning electron microscope photograph (3000x magnification) of the composite particles of Example 4 is shown in Figure 1.
[0086] [Comparative Example 1-4] Composite particles of Comparative Examples 1-4 were obtained in the same manner as in Example 1, except that no surface treatment compound was used and the cellulose derivative particles were changed to those shown in Table 4 below.
[0087] [Tactile feel (smoothness)] The tactile sensation of the Examples and Comparative Examples was evaluated by a panel of five experts. Each composite particle was touched and evaluated comprehensively on a scale of 1 to 5 in terms of both smoothness and moistness. The average score of the five experts was calculated and evaluated according to the following criteria. The evaluation results are shown in Tables 1-4 below as tactile sensation (smoothness). Good: 5, Fair: 4, Average: 3, Fair: 2, Bad: 1
[0088] [Texture (smooth)] The tactile sensation of the Examples and Comparative Examples was evaluated by a sensory panel of five experts. Each composite particle was touched and the smooth sensation was evaluated comprehensively on a scale of 1 to 5. The average score of the five experts was calculated and evaluated according to the following criteria. The evaluation results are shown in Tables 1-4 below as the smooth sensation. Good: 5, Fair: 4, Average: 3, Fair: 2, Bad: 1
[0089] [Water buoyancy] The water buoyancy of the composite particles of the examples and comparative examples was measured. Specifically, 1 g of sample was precisely weighed and added to 50 mL of water, and the mixture was mixed and stirred at a rotation speed of 100 rpm or more for 30 seconds or more. After that, the mixture was left to stand for 30 seconds or more, and the particles floating in the water were collected and dried, and then their weight was measured. The weight of the particles before mixing and stirring with water was set to 100, and the ratio of the weight of the particles floating in the water after drying was shown in Table 1-4 below as the water buoyancy (%). The higher the value, the higher the evaluation.
[0090] [Floatability in isododecane] The floatability in isododecane was measured for the composite particles of the Examples and Comparative Examples. Specifically, 1 g of sample was precisely weighed and added to 50 mL of isododecane, followed by mixing and stirring at a rotation speed of 100 rpm or higher for 30 seconds or longer. The mixture was then allowed to stand for 30 seconds or longer, and the particles floating in the isododecane were collected, dried, and then weighed. The weight of the particles before mixing and stirring with isododecane was set to 100, and the ratio of the weight of the particles floating in isododecane after drying was shown in Table 1-4 below as the floatability in isododecane (%). The smaller the value, the higher the evaluation.
[0091] [Table 1]
[0092] [Table 2]
[0093] [Table 3]
[0094] [Table 4]
[0095] Details of the compounds shown in Tables 1-4 are as follows: Cellulose acetate particles: Daicel Corporation, total substitution degree 2.4, average particle diameter 7.1 μm, sphericity 0.97, surface smoothness 100%, weight average molecular weight 173,000 Cellulose acetate propionate particles: Daicel Corporation, acetyl substitution degree 0.18, propionyl substitution degree 2.40, average particle size 9.5 μm, sphericity 0.95, surface smoothness 100%, weight average molecular weight 152,000 Cellulose acetate butyrate particles: Daicel Corporation, acetyl substitution degree 2.130, butyryl substitution degree 0.71, average particle size 8.2 μm, sphericity 0.96, surface smoothness 100%, weight average molecular weight 139,000 Ethyl cellulose particles: Daicel Corporation, total substitution degree 2.5, average particle size 7.7 μm, sphericity 0.97, surface smoothness 100%, weight average molecular weight 182,000 Distearyldimethylammonium chloride: Sanyo Chemical Industries, Ltd. (trade name: "Cation DSV") Alkyltrimethylammonium chloride: Nikko Chemical Co., Ltd. product name "CA-2580" Stearyltrimethylammonium chloride: Nikko Chemical Co., Ltd. product name "CA-2450" Potassium stearate: Potassium stearate manufactured by NOF Corporation, trade name "NonSal SK-1" Sodium stearate: NOF Corporation sodium stearate, trade name "NonSal SN-1" Polyoctanium-67: Cationic polymer manufactured by Dow, product name "SOFTCAT polymer SL-30" Polyoctanium-61: Cationic polymer manufactured by NOF Corporation, product name "Lipidure-S"
[0096] As shown in Tables 1-4, the composite particles of the Examples were evaluated as having a higher tactile sensation than the composite particles of the Comparative Examples. Furthermore, all of the composite particles of the Examples floated in water and settled in isododecane, demonstrating their excellent affinity with hydrophobic solvents. These evaluation results clearly demonstrate the superiority of the present disclosure. [Industrial Applicability]
[0097] The composite particles described above can be applied to the production of various cosmetic compositions.
Claims
1. The present invention has cellulose derivative particles and a coating film covering the surfaces of the particles, The composite particle, wherein the coating is formed from a surface treatment compound that is soluble in water and / or an organic solvent.
2. The composite particle according to claim 1 , wherein the organic solvent is an alcohol.
3. 2. The composite particle according to claim 1, wherein the surface treatment compound is one or more selected from the group consisting of cationic surfactants, fatty acid soaps, and cationic polymers.
4. The composite particle according to claim 1, wherein the surface treatment compound is one or more selected from the group consisting of distearyldimethylammonium chloride, behenyltrimethylammonium chloride, stearyltrimethylammonium chloride, potassium stearate, sodium stearate, polyoctanium-61, and polyoctanium-67.
5. 2. The composite particle according to claim 1, wherein the content of the surface treatment compound is 0.1% by weight or more and 20% by weight or less.
6. 2. The composite particle according to claim 1, wherein the cellulose derivative has an alkoxy group having 2 to 20 carbon atoms or an acyl group having 2 to 40 carbon atoms.
7. 2. The composite particle according to claim 1, wherein the cellulose derivative is cellulose acylate.
8. 2. The composite particle according to claim 1, wherein the cellulose derivative is cellulose acetate.
9. The composite particle according to claim 1 , wherein the cellulose derivative has a total degree of substitution of 0.7 or more and 3.2 or less.
10. 2. The composite particle according to claim 1, wherein the cellulose derivative particles have an average particle size of 0.08 μm or more and 100 μm or less, a sphericity of 0.7 or more and 1.0 or less, and a surface smoothness of 80% or more and 100% or less.
11. A cosmetic composition comprising the composite particles according to any one of claims 1 to 10.
12. a mixing step of stirring and mixing the cellulose derivative particles and the surface treatment compound in a solvent capable of dissolving the surface treatment compound; The method for producing composite particles according to claim 1 , further comprising, after the mixing step, a drying step of washing and drying the solid content containing the cellulose derivative particles.
13. The method according to claim 12, wherein the solvent is water or an alcohol.
14. The method according to claim 12, wherein the amount of the surface treatment compound added is 0.1% by weight or more and 20% by weight or less based on the weight of the cellulose derivative particles.